Pemberdayaan Masyarakat Desa Dudakawu Menuju Mandiri dan Berdaya Saing melalui Program Desa Wirausaha: indonesia - Febriansyah, Ahmad Diva; Bayu, Muhammad Bayu Nugroho; Sarwido, Sarwido; Septiarani, Diva Herninda; Prasetyo, Doni Agung; Akhis, Muhammad Ilma Akhis; Maknun, Muhammad Jauharul; Almajid, Ahmad Afan; Zahira, Tiara; Raffi, Muhamad Faizal; Putra, Fadhil Athalah; Pangestu, Binar Ageng Raganta; Haq, Muhammad Izzul; Hartoyo, Nindiya Ika Nugraha; Agustina, Hera Khilya; Ilma, Safira Putri Zidni (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Located in Kembang Subdistrict, Jepara Regency, Dudakawu Village possesses significant economic potential. However, its development is hindered by challenges such as inadequate entrepreneurial skills, ineffective marketing strategies, and limited access to digital technology. To overcome these issues, the PPK Ormawa Team of the Student Executive Board from the Faculty of Science and Technology at Unisnu Jepara initiated the "Entrepreneurial Village" program as a community service project. The program aims to improve entrepreneurial skills, enhance the competitiveness of local products, and broaden market access through digital transformation. This initiative utilized several strategies, including entrepreneurship workshops, the establishment of UMKM (Micro, Small, and Medium Enterprises) groups, product branding training, digital marketing education, and the development of innovative products. Activities were carried out through a collaborative approach involving academics, students, local authorities, and the community. Periodic evaluations were conducted using pre- and post-activity questionnaires, interviews, and direct observations to measure the program’s effectiveness in enhancing community skills and business activities. The findings reveal that more than 70% of participants improved their knowledge of entrepreneurship and digital marketing. The UMKM community established during the program served as a collaborative platform for local entrepreneurs, while products such as banana stem chips and the village’s specialty coffee gained added value and greater competitiveness in regional markets through branding and digital marketing efforts. This program has contributed significantly to sustainable, community-driven economic empowerment and offers a replicable model for other villages.